Development and Analysis of a Global Refractive Index of Water Data Layer for Spaceborne and Airborne Bathymetric Lidar - James T. Dietrich; Christopher E. Parrish (Earth and Space Science)
Abstract After over a half‐century of development, bathymetric lidar is a mature and widely used technology for mapping the littoral zone in support of nautical charting, benthic habitat assessment, inundation modeling and other applications. In 2018, bathymetric lidar transitioned from a purely airborne technology to also a spaceborne capability with the launch of NASA's ICESat‐2 satellite. An important aspect of obtaining accurate seafloor elevations and horizontal coordinates in bathymetric lidar is refraction correction, which corrects for the change in the speed and direction of the laser at the air‐water interface. Unfortunately, data on the refractive index of seawater needed for correction are largely lacking, especially over global extents, which are required for ICESat‐2 bathymetry. This study developed and evaluated a new global refractive index of water data layer. A two‐phased sensitivity analysis was conducted to investigate how systematic and random uncertainties in the refractive index layers impact bathymetric lidar uncertainty. We then developed the global refractive index of water layer using global marine data sets and evaluated it using a combination of Argo Float data and in situ refractometer measurements. The results provide a strong indication of the usefulness of the global refractive index layer, which is currently being implanted into the workflow for generating a new ICESat‐2 bathymetric data set (ATL24). To benefit other studies, the global refractive index layer is publicly available. Future improvements are possible, leveraging crowd‐sourced data collection to continually improve the spatial resolution and nearshore accuracy of the refractive index data set.